1990
DOI: 10.2136/sssaj1990.03615995005400030010x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Photoelectron Spectroscopy as a Tool to Differentiate Silicon‐Bonding State in Amorphous Iron Oxides

Abstract: An x‐ray photoelectron spectroscopy (XPS) study was conducted to: (i) compare the Si (2p) and O (1s) peaks of selected Si‐containing minerals, and (ii) evaluate the application of XPS in identifying probable Si‐bonding environments in Si‐containing ferrihydrites. For silica gel, the Si (2p) and O (1s) XPS peaks occurred at 104.0 and 534.2 eV, respectively; with biotite, these peaks occurred at 102.8 and 532.4 eV. The difference in the Si (2p) binding energies between silica gel and biotite was attributed to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
5
31
1
Order By: Relevance
“…The peak at 530 eV was assigned to O(ls) bound in ferric oxides (Mclntyre and Zetaruk, 1977). The shoulder at higher energy was attributed to O(1 s) coordinated in hydroxyl groups associated with Fe (Vempati et al, 1990). The Si(2s) peak occurred at 153.3 eV (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at 530 eV was assigned to O(ls) bound in ferric oxides (Mclntyre and Zetaruk, 1977). The shoulder at higher energy was attributed to O(1 s) coordinated in hydroxyl groups associated with Fe (Vempati et al, 1990). The Si(2s) peak occurred at 153.3 eV (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Hence the particle is primarily composed of surface area and near-surface area, and this suggests that the bulk structure is of lesser significance. Vempati et al (1990) argued that >90% of associated Si is structure bound in a ferrihydrite precipitated at a Si/ Fe molar ratio of 1.0 (see Vempati et al, 1990, Figure 3). This conclusion is based on the XPS Si(2p) signal, which occurs in an energy range where Fe(3s) has a satellite peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) indicated that Si content (at least in the range studied here) had a small effect on the biotransformation of ferrihydrite in terms of rate, extent, and biomineralization. Sorbed Si exists as a surface complex [-Fe-O-Si(OH) 3 ] on ferrihydrite at lower Si/Fe ratios (Ͻ0.05) and as a structural constituent (-Fe-O-Si-bonds) when Si/Fe Ͼ0.10 (Vempati et al, 1990). Ferrihydrite exhibits a higher affinity for phosphate than silicate [as -Fe-O-Si(OH) 3 ]; and PO 4 3Ϫ displaces H 3 SiO 4 Ϫ easily from ferrihydrite surfaces (Parfitt, 1978;Vempati and Loeppert, 1989;Parfitt et al, 1992).…”
mentioning
confidence: 99%
“…A possible explanation for this lower binding energy shift could be that silica or silicate was bonded with metal ions. For example, Vempati et al (1990) discovered that, when ferrihydrite co-precipitated with silica, the binding energy of silicon was shifted lower to 100.8 eV. Moreover, a study done by Gonzalez-Elipe et al (1988) showed that, in the phyllosilicate minerals framework, substitution of Al or Mg for Si conferred net negative charge to the tetrahedral sheet, thus lowered the photoelectron binding energies of silicon and oxygen.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%